Cassava starch modified by oxidation: Physical and chemical properties and texture profile of the gels (Research, Society and Development, 2020)
Starch is an important compound in human food, as it is a great source of energy. However, native starch has limitations that make it difficult to use, so it can be modified to acquire stability, improve as rheological characteristics of the masses or texture of the gels, among others. The objective of this study was to evaluate the chemical composition of native (3 brands) or modified by oxidation (potassium permanganate, sodium hypochlorite or citric acid) cassava starch, as well as the texture profile and the physical and chemical properties of the gels obtained therefrom. Because of the lower amylose content and the intermediate texture parameters of the gels, a commercial native starch brand was considered more suitable for chemical modification. The starch modification by oxidation with citric acid or sodium hypochlorite resulted in gels with less firmness, gumminess and adhesiveness and higher clarity, cohesiveness, resilience and elasticity than native starches. In addition, the nutritional value of the starch was not altered by chemical modification. The utilization of potassium permanganate modified starch resulted in gels with physical, chemical and appropriate texture, but it had excessively dark coloration, which limits its use in processed foods. It is recommended the use of modified starches by oxidation in food toppings, salad dressings, mayonnaise, as binding agents in confectionery products or as emulsifiers.